O CUIDADO DE ENFERMAGEM AO EGRESSO DA TERAPIA INTENSIVA: REFLEXOS NA PRODUÇÃO CIENTÍFICA NACIONAL DE ENFERMAGEM PEDIÁTRICA NA DÉCADA DE 90. - Ivone Evangelista Cabral; Flavio Dias da Silva (Universidade Federal de Goias, 2001)
The incidence on nursing national scientific production concerning child care after pediatric intensive care in the nineties, is the object being investigated on this research. Raising the incidence of scientific production implicit in the object under investigation is the aim of this research that claims either quantity and quality aspects, developed according documental analysis method. National scientific production shows the nurses worries on how to deal with these children, whether being hospitalized, coming to medical appointments or at home. Besides that, it reveals nurses invisibility when it comes to home care for these children, and also the improvement of families abilities and duties in dealing with technological care associated to usual care